Parenting and adolescent problem behaviors: A comparative study of sons and daughters in Thailand - Rhucharoenpornpanich O. (2017)
Objective: Investigates parenting practices and the reported sexual and delinquent behaviors among Thai adolescents, by focusing on the difference between sons and daughters. Material and Method: Data were derived from 420 families whose adolescents aged 13-14 were randomly selected from seven districts in Bangkok using the probability proportional to size (PPS) method. Interviews were conducted with one parent and one adolescent. Results: Female adolescents reported higher levels of parental monitoring, parental rules, communication about sex, and parental disapproval of sex, as compared to males. There were no gender differences in the reported sexual and delinquent behaviors among the adolescents. For males, high levels of parental monitoring, greater perception of parent disapproval of sex, and being raised by authoritative parents were associated with less delinquent behaviors. Among females, parental monitoring and parental closeness served as protective factors against sexual and delinquent behaviors. Conclusion: The findings from the present study point to the importance of promoting family institution and parents' childrearing. These findings should be useful for developing a body of knowledge and understanding on adolescent rearing among Thai parents.